2005
DOI: 10.1111/j.1365-2036.2005.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gastro‐oesophageal reflux disease symptoms: a community study

Abstract: Summary Aim:  To examine the prevalence of gastro‐oesophageal reflux disease symptoms and potential risk factors among community subjects. Methods:  A questionnaire was sent to 4000 subjects, stratified by age, gender and ethnicity to be representative of the local population. Gastro‐oesophageal reflux disease symptoms were defined as at least weekly heartburn or acid regurgitation. Results:  2231 responded (59%), 691 refused to participate and seven were incomplete. 1533 (41%) were evaluable (637 male, mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
3
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 39 publications
5
70
3
14
Order By: Relevance
“…A study conducted by Jansson et al reported that patients with depression had 1.7-fold risk of GERD, those with anxiety had a 3.2-fold increased risk, while in those with both the risk was had 2.8-fold. 24 Similar to other studies, 8,13,21,25 in our study too, women with GERD-related symptoms were more commonly found to have depressive and anxiety disorders.…”
Section: Gerd and Psychological Co-morbiditysupporting
confidence: 77%
“…A study conducted by Jansson et al reported that patients with depression had 1.7-fold risk of GERD, those with anxiety had a 3.2-fold increased risk, while in those with both the risk was had 2.8-fold. 24 Similar to other studies, 8,13,21,25 in our study too, women with GERD-related symptoms were more commonly found to have depressive and anxiety disorders.…”
Section: Gerd and Psychological Co-morbiditysupporting
confidence: 77%
“…The positive family history suggests either a genetic predisposition for GERD or the influence of nongenetic environmental factors. Recent studies reporting a higher incidence of GERD in monozygotic twins support a contribution of genetic factors to this disease [26,27,28]. In future studies, the family history on the question for presence of GERD in the patient’s father and siblings should be included.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to controls, RE patients were twice as likely to report drinking at least one alcoholic drink per month. There were no significant associations between wine or liquor consumption and RE (Mohammed et al, 2005;Nocon et al, 2006;Anderson et al, 2009). Interestingly, the highest intake of beer (≥11.928 L per week) was inversely associated with RE (Anderson et al, 2009).…”
Section: Introductionmentioning
confidence: 79%